Facilitated self-reported anaesthetic medication errors before and after implementation of a safety bundle and barcode-based safety system. (December 2018) - Bowdle, T.A.; Jelacic, S.; Nair, B.; Togashi, K.; Caine, K.; Bussey, L.; Kruger, C.; Grieve, R.; Grieve, D.; Webster, C.S.; Merry, A.F.
Abstract: Background: Anaesthetic medication administration errors are a significant threat to patient safety. In 2002, we began collecting data about the rate and nature of anaesthetic medication errors and implemented a variety of measures to reduce errors. Methods: Facilitated self-reporting of errors was carried out in 2002–2003. Subsequently, a medication safety bundle including 'smart' infusion pumps were implemented. During 2014 facilitated self-reporting commenced again. A barcode-based medication safety system was then implemented and the facilitated self-reporting was continued through 2015. Results: During 2002–2003, a total of 11 709 paper forms were returned. There were 73 reports of errors (0.62% of anaesthetics) and 27 reports of intercepted errors (0.23%). During 2014, 14 572 computerised forms were completed. There were 57 reports of errors (0.39%) and 11 reports of intercepted errors (0.075%). Errors associated with medication infusions were reduced in comparison with those recorded in 2002–2003 ( P <0.001). The rate of syringe swap error was also reduced ( P =0.001). The reduction in error rate between 2002–2003 and 2014 was statistically significant ( P =0.0076 and P =0.001 for errors and intercepted errors, respectively). From December 2014 through December 2015, 24 264 computerised forms were completed after implementation of a barcode-based medication safety system. There were 56 reports of errors (0.23%) and six reports of intercepted errors (0.025%). Vial swap errors in 2014–2015 were significantly reduced compared with those in 2014 ( P =0.004). The reduction in error rate after implementation of the barcode-based medication safety system was statistically significant ( P =0.0045 and P =0.021 for errors and intercepted errors, respectively). Conclusions: Reforms intended to reduce medication errors were associated with substantial improvement.